Nobility criteria as a measure of Kafa'ah in marriage - Mesarah, Baiq Maya; Wathoni, Lalu Muhammad Nurul (MID Publisher International, 2024)
During the royal era, it was common for marriages to require both partners to come from the nobility. This practice could be based on access to education and aspects of life worth that were more available to the nobility. So, a nobleman's marriage must be with a nobleman to get pure offspring. As in Indonesia, women with noble status are